Case study on the application of Scrum methodology in a technology startup of Minas Gerais (Research, Society and Development, 2021)
The ways of managing projects have been constantly improving because of globalization. In that context, the Agile Manifesto emerged, which allowed the creation of several agile methodologies that have varied characteristics such as dynamism, adaptability and productivity, Scrum being one of them. Therefore, the objective of this work is to verify the impact of this framework in all areas of a Lean Startup, which has a journey designed in Marketing and Sales, going through the Customer Experience, up to the Products and Development areas, and also, verifying terms of productivity and quality of activities carried out in this startup located in the state of Minas Gerais. In order to achieve this objective, semi-structured interviews were carried out in which it is possible to analyze the impacts of the methodology in the execution of the tasks of all employees involved. At the end of the study, one can see positive points generated by the implementation of the methodology, such as organization and prioritization, and the difficulties encountered, such as time management, were also pointed out.